Cystic Medial Degeneration Leading to Popliteal Artery Aneurysm With Distal Embolization - Victor Cabrera‐Bou; Tuleagh Innes‐Gawn; Adam Levitt; Julio Calderin (Clinical Case Reports, 2026)
ABSTRACT Cystic medial degeneration is a rare process that can cause aneurysmal degeneration of arteries including the aorta, iliac arteries, femoral arteries, and popliteal arteries. In this report we discuss a case of a popliteal artery aneurysm caused by cystic medial necrosis that led to distal embolization. Right lower extremity excision of the popliteal artery aneurysm with placement of an interposition graft using reversed great saphenous vein was used in our case and can be used in other cases for treatment and prevention of further embolization.